Radial nerve palsy caused by a rapidly growing intramuscular hematoma in an infant with biliary atresia: a case report - Kohei Kawahara; Koki Ota; Shingo Numoto; Nami Nakamura; Ryosuke Miyamoto; Hitoshi Honma; Yusuke Morishita; Katsuhisa Kawanami; Nozomi Matsushita; Shoko Kato; Kenitiro Kaneko; Akihisa Okumura; et al. (BMC, 2023)
Abstract Background Biliary atresia (BA) is a rare cause of persistent jaundice in infants that can result in vitamin K malabsorption and vitamin K deficiency bleeding (VKDB). We present an infant with BA who developed a rapidly growing intramuscular hematoma in her upper arm after a vaccination which caused a radial nerve palsy. Case presentation An 82-day-old girl was referred to our hospital because of a rapidly growing left upper arm mass. She had received three doses of oral vitamin K before age 1 month. At age 66 days, she received a pneumococcal vaccination in her left upper arm. On presentation, she showed no left wrist or finger extension. Blood examination revealed direct hyperbilirubinemia, liver dysfunction, and coagulation abnormalities, indicating obstructive jaundice. Magnetic resonance imaging showed a hematoma in the left triceps brachii. Abdominal ultrasonography revealed an atrophic gallbladder and the triangular cord sign anterior to the portal vein bifurcation. BA was confirmed on cholangiography. VKDB resulting from BA in conjunction with vaccination in the left upper arm were considered the cause of the hematoma. The hematoma was considered the cause of her radial nerve palsy. Although she underwent Kasai hepatic portoenterostomy at age 82 days, the obstructive jaundice did not sufficiently improve. She then underwent living-related liver transplantation at age 8 months. The wrist drop was still present at age 1 year despite hematoma resolution. Conclusions Delayed detection of BA and inadequate prevention of VKDB can result in permanent peripheral neuropathy.